Growth of Limited Liability Partnerships (LLPs) in India with special reference to Innovative Vehicle for Entrepreneurial Development: The impact of legislative acts on the growth and support of LLPs in India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The purpose of this research is to examine how the Company Act of 2013 and the Goods andServices Tax Act of 2017 have affected the development of LLPs in India. The data in this research isanalysed and interpreted using both descriptive and inferential statistics. The study indicated that therewere twice as many LLPs in the service industry than there were in manufacturing or agriculture,respectively. This study has reached its conclusion and offers suggestions to the Indian federal, state,and regional governments to encourage the formation of new limited liability partnerships (LLPs). Localand foreign company owners, both established and hopeful, may take advantage of them via subsidisedloans, tax rebates, and other types of financial help. By increasing India's business friendliness andgiving investors more security, this bill helps the country attract investment.